Ultrasonographic diagnosis of pregnancy and estimation of fetal numbers in ewes - ANILKUMAR, R; IYUE, M; PREMA, N; SREEKUMAR, C (The Indian Journal of Animal Sciences, 2014)
Ultrasound scanning is one of the methods to diagnose pregnancy and it also helps in identifying twin bearing ewes, which requires special care during the last stages of pregnancy. Thirty-six ewes were examined by rectal probe and 493 ewes were examined with trans-abdominal probe. Sequential scanning with rectal probe from 3–6 weeks of pregnancy revealed very clear fetal movements and heart beat at fifth week. Using trans-abdominal probe 451 ewes out of 493 ewes scanned were diagnosed as pregnant with 23 of them showing twin pregnancy. Accuracy of identifying pregnant ewes at 60–75 days of pregnancy was 98.00% with 2.00% false positive cases. The accuracy of identifying twin was 69.97% and was more in Nilagiri ewes. No twin was diagnosed in Dorset Nilagiri cross ewes. Those ewes which were diagnosed to have twins were given additional concentrate feeding and all of them survived and gave birth to twin except one which had still born twin lambs.